2019
DOI: 10.1128/aac.00866-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Identifies Novel Pseudomonas aeruginosa Resistance Genes under Selection during Inhaled Aztreonam Therapy In Vivo

Abstract: Inhaled aztreonam is increasingly used for chronic Pseudomonas aeruginosa suppression in patients with cystic fibrosis (CF), but the potential for that organism to evolve aztreonam resistance remains incompletely explored. Here, we performed genomic analysis of clonally related pre- and posttreatment CF clinical isolate pairs to identify genes that are under positive selection during aztreonam therapy in vivo. We identified 16 frequently mutated genes associated with aztreonam resistance, the most prevalent be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…First, strain PAO1-AzEvB8 that was the focus of the present study was not an actual clinical isolate and it is unclear how frequently mutants arise that have both mexR and mexEF mutations. As mentioned above, literature suggests that mexR mutations are very common in CF, and that clinical isolates can display varying degrees of mexE gene expression [20,22,24,33,36,37], so we feel that this study still has relevance to real-world P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…First, strain PAO1-AzEvB8 that was the focus of the present study was not an actual clinical isolate and it is unclear how frequently mutants arise that have both mexR and mexEF mutations. As mentioned above, literature suggests that mexR mutations are very common in CF, and that clinical isolates can display varying degrees of mexE gene expression [20,22,24,33,36,37], so we feel that this study still has relevance to real-world P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 88%
“…P. aeruginosa with mutations in nalD and mexR overexpress the MexAB-OprM efflux pump, rendering them multidrug resistant [17,19,21]. Moreover, mutations in these two genes have been found in anywhere from 7-47% of clinical isolates in various studies [20][21][22][23][24]. Importantly, strains with mutations in nalD and mexR evolved under aztreonam selection showed an increased virulence in vivo, challenging the longstanding theory that antibiotic resistance mutations inherently pay fitness costs that attenuate virulence (Jorth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Being one of the top three globally most prevalent nosocomial infectious agents and equipped with virulence and resistance, P. aeruginosa’s infections require additional resources and time for patients to recover (Pires, et al 2018 ; Moradali et al 2017 ; Juan et al 2017 ). Countless studies have reported the extent of antibiotic resistance due to multiple factors ranging from over-prescription, self-medication, and abuse of antibiotics on farms, all ultimately affecting the patients’ survival and recovery (Xipell 2017 ; McLean 2019 ; Pang 2019 ; Frieri et al 2017 ; Qiao 2018 ; Karkman 2018 ). While the lack of vaccines for superbugs was not even an area of interest for academia as well as an industry until recently (Rappuoli et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the top three globally most prevalent nosocomial infectious agents and equipped with virulence and resistance, P. aeruginosa's infections require additional resources and time for patients to recover [62][63][64] . Countless studies have reported the extent of antibiotic resistance due to multiple factors ranging from over-prescription, self-medication, and abuse of antibiotics on farms, all ultimately affecting the patients' survival and recovery [65][66][67][68][69][70] . While the lack of vaccines for superbugs was not even an area of interest for academia as well as an industry until recently 71 .…”
Section: Discussionmentioning
confidence: 99%